A comparative morphological study of the terminalia of Scarabaeoidea (Coleoptera) with a special emphasis on Pleurosticti - Cristóvão, Joana Pequito (2021)
The Scarabaeoidea comprises over 35,000 known species worldwide within 12 families and, despite being an important group in terms of ecosystem services as well as the long and complex history in terms of classification, its taxonomy remains unstable. Various morphological characters and character complexes have been used to help inform on the higher taxonomy of the superfamily and, despite few efforts, knowledge about the terminalia of Scarabaeoidea remains limited. The terminalia, especially that of the males, has long been known to bear informative characters that allow even cryptic species to be recognised. The main impediment for a comparative study of the terminalia of Scarabaeoidea is that specialists of different taxa utilise different terminologies for supposedly homologous structures. In the first chapter of this study the terminology of the terminalia of males and females is discussed and homogenised, culminating in a Scarabaeoidea-specific glossary, including synonyms for each term. The following structures are described here for the first time: “bursa spiculare”, “spicula”, “mesobursite” and “pseudocoxite (type I and type II)”. A standardised dissecting protocol, including adjustments to the general technique, depending on the taxon, is provided for the first time. The external sexual dimorphism of some of the most difficult groups to sex are also provided. In the second chapter, an indepth study of male and female terminalia of Pleurosticti was performed, based on, where possible, the type species for all tribes and subtribes, as well as taxa which have been synonymised with these. The main potentially informative patterns for different taxa are discussed and compared to those of other Scarabaeoidea. A wealth of characters and character states, some of which novel, were found in the terminalia of both males and females. It was found that Dynastinae and Rutelinae are characteristically indistinguishable from one another, with many character states overlapping between the two (currently accepted) subfamilies. Cetoniinae (including Trichiini and Valgini) were found to have a unique character, a bursa spiculare. Valgini was found to be subdivided into two main groups which require further analyses. Melolonthinae was found to be very heterogeneous, with some taxa most similar to Dynastinae-Rutelinae and others to Cetoniinae, therefore requiring further studies and analyses. The male of Pachypodini was found to share two unique characters: a bursa spiculare, unique to Cetoniinae, and a spicula, unique to some melolonthine taxa as well as other non-Pleurosticti Scarabaeoidea.